Determinants of prostate cancer screening uptake among men aged 40 years and above in Ruiru sub county, Kenya - Mureithi, Margaret; K'Odhiambo, Maurice Onditi; Mureithi, James; Murigi, Mary (International Journal Of Community Medicine And Public Health, 2022)
Background: The Kenya demographic and health survey in the year 2014 indicated that only two-thirds of Kenyan men age 15-49 have heard of prostate cancer. In addition, only three percent of males aged 40 years and above have ever had a prostate cancer screening. This signifies that prostate cancer screening is still uncommon among Kenyan men despite prostate cancer being ranked third among commonly diagnosed cancers globally. Methods: The study adopted a descriptive cross-sectional design. Quantitative data was collected using a semi-structured questionnaire. Collected data was analysed using Statistical package for data analysis (SPSS). Thereafter, descriptive statistics were presented by the use of mean, percentages and proportions while inferential statistics that is standard deviation and Chi square values were used to determine the statistical significance (p≤0.05). Results: This study shows that most men (87%) were aware of prostate cancer. Marital status p=0.007, occupation p=0.019, fear p=0.005, shyness/embarrassment p=0.034 and the level of education p=0.005 significantly influenced the uptake of cervical cancer screening among males aged 40 years and above. Noteworthy, education about prostate cancer screening did not significantly influence the males under this age brackets decision to get the prostate cancer screening. Conclusions: More efforts are needed to encourage adult male who are highly at risk of prostate cancer to go for voluntary screening as early detection have been shown to improve the disease outcome. In addition, a dire need for increased awareness of prostate cancer screening to demystify fear by the stakeholders that is, the healthcare system, Ministry of Health, faith-based organizations, family as well as friends.